Dialectical behaviour therapy skills group including stigma management: a pilot with sexual and gender minority veterans. (2nd November 2021) - Skerven, Kim; Mirabito, Lucas; Kirkman, Mackenzie; Shaw, Beth
Abstract: As a principle-driven treatment, dialectical behaviour therapy (DBT) offers concepts and strategies that can be flexibly applied to address unique types of invalidation, such as stigma experienced by marginalized groups. A pilot DBT skills training group that included material on using skills to dialectically manage the effects of stigma was conducted with four sexual and gender minority (SGM) veterans. The group included standard DBT skills along with explicitly teaching about stigma commonly faced by SGM individuals and ways to apply DBT skills to the experiences of stigma. This pilot group was conducted to determine the acceptability of such a group as well as its effects on symptoms (depression, emotion regulation), use of DBT skills in daily living, and the psychological burden of stigma-related experiences. The group was well-received by participants; outcomes suggest promising trends in reducing psychological distress and increasing use of DBT skills to cope. Implications for clinical practice using a dialectical approach to stigma management and future directions are provided. Key learning aims: (1) Readers will learn about how dialectical behaviour therapy can be used to help sexual and gender minority clients effectively manage the effects of minority stress. (2) Readers will learn how taking a dialectical perspective on managing minority stress can be effective. (3) Readers will learn how delivering dialectical behaviour therapy in a manner contextualized within the clients' experience can be effective in managing mental health symptoms.